Effect of Anatase/Rutile TiO2 Phase Composition on Arsenic Adsorption - Gupta K.K.; Singh N.L.; Pandey A.; Shukla S.K.; Upadayay S.N.; Mishra V.; Srivastava P.; Lalla N.P.; Mishra P.K. (My University, 2025)
Nano TiO2 particles with different phase composition were synthesised using sol-gel method. Two different solvent were used for gelation. Effect of gelation temperature and to time on anatase/rutile phase formation had been studied. Particles crystallinity, crystal size, surface area, pore size had been calculated by x-ray diffraction, Raman spectroscopy, Brunauer-Emmett-Teller (BET) surface area) theory, and transmission electron microscopy analysis. How change in crystal size, surface area, pore size with respect to phase change also has been studied. Arsenate and arsenite removal by TiO2 particles of different phase compositions had been investigated by atomic absorption spectroscopy. Some parameters such as the contact time and the pH of the solution, which could affect the magnitude of adsorption, were examined. Sorption data have been interpreted in terms of the Freundlich and Langmuir equations. [Supplemental materials are available for this article. Go to the publisher's online edition of the Journal of Dispersion Science and Technology to view the free supplemental file.]. © 2013 Copyright Taylor and Francis Group, LLC.